Permissive expansion and homing of adoptively transferred T cells in tumor‐bearing hosts. Issue 2 (28th January 2015) - Perez, C.; Jukica, A.; Listopad, J.J.; Anders, K.; Kühl, A.A.; Loddenkemper, C.; Blankenstein, T.; Charo, J.
<x xml:space="preserve">Abstract</x> Activated T cells expressing endogenous or transduced TCRs are two cell types currently used in clinical adoptive T‐cell therapy. The ability of these cells to recognize their antigen, expand and traffic to the tumor site are the initial steps necessary for successful therapy. In this study, we used in vivo bioluminescent imaging (BLI) of Renilla luciferase (RLuc) expressing T cells to evaluate the ability of adoptively transferred T cells to survive, expand and home to tumor site in vivo. Using this method, termed RT‐Rack (Rluc T cell tracking), we followed T‐cell response against tumors in vivo. Expansion and homing of adoptively transferred T cells were antigen dependent, but independent of the host immune status. Moreover, we successfully detected T‐cell response to small and large tumors, including autochthonous liver tumors. The adoptively transferred T cells were not ignorant or excluded in a partially tolerant host, which expressed low level of the target in the periphery. Using T cell receptor (TCR)‐engineered T cells, we showed the ability of these cells to respond in tumor‐bearing hosts by expanding and homing to the tumor site. In all these models, the host immune status, the nature of the tumor or of the antigen, the tumor size and the presence of the targeted antigen in the periphery did not prevent the adoptively transferred T cells from responding by expanding and homing to the tumor. However, T cells had higher expression of the inhibitory receptor PD1 and reduced functional activity when a self‐antigen was targeted.